Musical analyses and musical exegesis the shepherd's melody in Richard Wagner's Tristan and Isolde - Nattiez, Jean-Jacques 1945- (University of Rochester Press, 2021)
Here translated for the first time, Jean-Jacques Nattiez's widely hailed comparative guide to the techniques of music analysis focuses on a single vivid passage from Wagner's Tristan and Isolde
Title from publisher's bibliographic system (viewed on 04 Jun 2021)
Keywords: Wagner, Richard / 1813-1883 / Tristan und Isolde; Wagner, Richard -- 1813-1883 -- Tristan und Isolde; Musical analysis; Musikalische Analyse; Melodie; Englischhorn